2019
DOI: 10.1038/s41564-019-0563-x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae residing in food vacuoles expelled by protozoa are more infectious in vivo

Abstract: Reprints and permissions information is available at www.nature.com/reprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 55 publications
(60 reference statements)
2
41
1
Order By: Relevance
“…In addition, OmpU, a major outer membrane protein that is needed for resistance to many stressors such as organic acids, bile, and AMPs as well as being a critical factor for the in vivo colonization of V. cholerae (Sperandio et al, 1995;Provenzano and Klose, 2000), plays a role in survival in protozoa. It was recently shown that OmpU is important for the expulsion of V. cholerae within food vacuoles of ciliate hosts, a fact that suggests that this protein might confer resistance to V. cholerae to the intra-phagosomal factors required for digestion (Espinoza-Vergara et al, 2019). Interestingly, it is also reported that OmpU is essential for V. splendidus host invasion and resistance to AMPs and is required for virulence in the oyster, Crassostrea gigas (Duperthuy et al, 2011).…”
Section: Intracellular Survival Of Vibrio Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, OmpU, a major outer membrane protein that is needed for resistance to many stressors such as organic acids, bile, and AMPs as well as being a critical factor for the in vivo colonization of V. cholerae (Sperandio et al, 1995;Provenzano and Klose, 2000), plays a role in survival in protozoa. It was recently shown that OmpU is important for the expulsion of V. cholerae within food vacuoles of ciliate hosts, a fact that suggests that this protein might confer resistance to V. cholerae to the intra-phagosomal factors required for digestion (Espinoza-Vergara et al, 2019). Interestingly, it is also reported that OmpU is essential for V. splendidus host invasion and resistance to AMPs and is required for virulence in the oyster, Crassostrea gigas (Duperthuy et al, 2011).…”
Section: Intracellular Survival Of Vibrio Sppmentioning
confidence: 99%
“…Similarly, mice infections performed with Mycobacterium ulcerans previously co-incubated with A. polyphaga led to enhanced pathogenicity (Azumah et al, 2017). In the case of Vibrio spp., it has recently been shown that their release in EFVs to the extracellular environment results in bacterial growth and colonization advantage in vitro and in vivo, respectively (Espinoza-Vergara et al, 2019). In addition, the use of a critical virulence factor in V. cholerae, OmpU, involved in colonization and resistance to low pH, AMPs, and bile, was shown to be involved in the release of EFVs from protozoa.…”
Section: The Impact Of Protozoan Predation On Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria packaging by Tetrahymena has mostly been studied for pathogens so far, including Legionella pneumophila , Salmonella enterica , Escherichia coli O157:H7, C. jejuni , and Vibrio cholerae [ 1 , 2 , 8 , 10 , 11 ]. Pathogenic bacteria are equipped with virulence factors that can facilitate resistance to digestion, but it has also been shown that at least some bacteria that are non-pathogenic to humans can be packaged by the social amoeba Dictyostelium discoideum [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic bacteria are equipped with virulence factors that can facilitate resistance to digestion, but it has also been shown that at least some bacteria that are non-pathogenic to humans can be packaged by the social amoeba Dictyostelium discoideum [ 6 ]. Bacterial packaging could promote the survival of bacteria in harsh environments or act as a reservoir, as pellets can stay intact for weeks [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%